Adaptation of child oral health education leaflets for Arabic migrants in Australia: a qualitative study - Amit Arora; Ibrahim Al-Salti; Hussam Murad; Quang Tran; Rhonda Itaoui; Sameer Bhole; Shilpi Ajwani; Charlotte Jones; Narendar Manohar (BMC, 2018)
Abstract Background The purpose of this study was to gain an in-depth understanding of Arabic-speaking mothers views on the usefulness of existing oral health education leaflets aimed at young children and also to record their views on the tailored versions of these leaflets. Methods This qualitative study was nested within a large ongoing birth cohort study in South Western Sydney, Australia. Arabic-speaking mothers (n = 19) with young children were purposively selected and approached for a semi-structured interview. Two original English leaflets giving advice on young children's oral health were sent to mother's prior to the interview. On the day of interview, mothers were given simplified-English and Arabic versions of both the leaflets and were asked to compare the three versions. Interviews were audio-recorded, subsequently transcribed verbatim and analysed by thematic analysis. Ethical approval was obtained from Human Research Ethics Committees of the former Sydney South West Area Health Service, University of Sydney and Western Sydney University. Results Mothers reported that simplified English together with the Arabic version of the leaflets were useful sources of information. Although many mothers favoured the simplified version over original English leaflets, the majority favoured the leaflets in Arabic. Ideally, a "dual Arabic - simplified English leaflet" was preferred. The understanding of key health messages was optimised through a simple layout and visual images. Conclusions There is a need to tailor oral health education leaflets for Arabic-speaking migrants. Producers of dental leaflets should also consider a "dual Arabic - simplified English leaflet" to improve oral health knowledge of Arabic-speaking migrants. The use of simple layout and pictures assists Arabic-speaking migrants to understand the content of dental leaflets.